2010
DOI: 10.3354/meps08500
|View full text |Cite
|
Sign up to set email alerts
|

Short-term movements and diving behaviour of satellite-tracked blue sharks Prionace glauca in the northeastern Atlantic Ocean

Abstract: Shifts in the movement, activity or behaviour of individual animals in relation to changing environmental landscapes play an important role in determining re-distribution patterns of populations. Such spatial dynamics are poorly understood for pelagic sharks despite the decline of many species due to overfishing. Satellite-linked archival transmitters were used to record the movements of blue sharks Prionace glauca for the first time in the northeast Atlantic. A total of 256 tracking days were recorded, with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 64 publications
(93 reference statements)
3
54
0
3
Order By: Relevance
“…3). While surface orientated behaviour has previously been documented for blue sharks [7,9], for example, a study in the Northeast Atlantic found that blue sharks can spend large periods of their time 'at or near the surface' [7]; the authors do not specify knifing behaviour. Here we specifically highlight the frequency and timing of knifing behaviour that has not been reported in previous studies, likely due to a combination of coarse resolution of binned depth data in PSAT tags (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). While surface orientated behaviour has previously been documented for blue sharks [7,9], for example, a study in the Northeast Atlantic found that blue sharks can spend large periods of their time 'at or near the surface' [7]; the authors do not specify knifing behaviour. Here we specifically highlight the frequency and timing of knifing behaviour that has not been reported in previous studies, likely due to a combination of coarse resolution of binned depth data in PSAT tags (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited examples in the literature where sharks are recorded spending considerable time in surface waters or are described as surface orientated [5][6][7], the behaviour whereby sharks 'knife' their dorsal fin through the water's surface (hereafter termed knifing behaviour) is largely unreported outside of the planktivorous sharks [8]. Tracking studies on blue sharks suggest that this species displays knifing behaviour regularly, as smart position only tags (SPOTs) successfully transmit multiple locations throughout the day [9,10] and popup satellite archival tags (PSATs) have described distinct surface-orientated behaviours [7].…”
Section: Background and Aimsmentioning
confidence: 99%
“…In the temperate waters of the North Atlantic, blue sharks of different size and sex display temporal and spatial segregation patterns; mating areas are observed in both sides of the North Atlantic, but pupping and nursery areas have only been encountered in the eastern North Atlantic (Casey, 1985;Stevens, 1990;Aires-da-Silva et al, 2008a). Recent satellite-tracking studies have supported that the movement pattern deployed by blue sharks in the northeast Atlantic is clearly influenced by seasonal changes in sea surface temperature and that juvenile and sub-adult sharks display a wider variety of short and longer range movements than previously known, suggesting a complex spatial dynamics and population structuring (Queiroz et al, 2010). Furthermore, a recent study of sharks in the open ocean exhibiting seasonal and spatial sexual segregation suggested that differential exploitation of the sexes is possible and could be a major contributor to population decline in pelagic sharks (Mucientes et al, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…Blue sharks are the most abundant sharks in some parts of the world, reaching 3 m in length, and they typically feed mostly on squid, fishes, and crustaceans [70,71]. Blue sharks move widely in areas such as the North Atlantic [72] and are distributed offshore in about the upper 350 m during daytime and at deeper depths at night (mostly 400-770 m) [71,[73][74][75]. Therefore, their foraging depths can directly overlap with the depth where the H. atlanticus was seen in the present study and where smaller individuals live [13].…”
Section: Journal Of Marine Biologymentioning
confidence: 99%